1962
DOI: 10.4141/cjps62-015
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARISON OF GROWTH, LIFE CYCLE AND CONTROL OF DIBOTRYON MORBOSUM (SCH.) TH. & SYD. ON PEACH AND PLUM IN NOVA SCOTIA

Abstract: A comparative study of Dibotryon morbosum (Sch.) Th. & Syd. on peach and plum showed the life cycle to be the same on both hosts. Peach knots were less prominent and produced very few mature perithecia. Plum inoculum was considered to be largely responsible for infections on the peach. The morphology and cultural characteristics of the isolates from the two hosts were similar. Ascospores from plum knots readily infected peach seedlings but those from peach knots did not infect peach or plum seedlings. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Drenching the seedlings with ascospore suspensions did not result in detectable infection in this study but has been successful in other investigations (2,6,11). Inoculation with conidia produced in culture has had limited success (11) but may merit further investigation.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Drenching the seedlings with ascospore suspensions did not result in detectable infection in this study but has been successful in other investigations (2,6,11). Inoculation with conidia produced in culture has had limited success (11) but may merit further investigation.…”
Section: Discussionmentioning
confidence: 61%
“…The disease is readily recognized by black stem-and branch galls, which support mature stromata of the causal fungus. On cultivated orchard crops, black knot causes losses in fruit production (2,5,10), but its impact on native Prunus spp. is unknown (3,12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that various strains of the pathogen may have some specificity to certain host plants. Gourley (1962) reported that ascospores from plum knots readily infected peach seedlings, but those from peach knots did not infect peach or plum seedlings. Similarly, Smith et al (1970) were unable to induce the black knot disease in P. domestica 'Stanley', using ascospores from Prunus serotina Ehrh.…”
Section: Introductionmentioning
confidence: 99%